Evaluation of fruit tree transpiration with heat flux sensor - Riczu, P.; Nagy, A.; Tamás, J. (International Journal of Horticultural Science, 2014)
One of the biggest professional challenges of the following years is to develop the water resource management for apple trees. In order to know the water consumption of plants, some traditional and modern methods could useful. In our research the sap flow measurement of the plants were carried out. We have analyzed the transpiration properties of the trees in the investigation period. In order to compare the transpiration of the trees, the leaf areas were scanned and evaluated. Beside these measurements, soil water properties were determined by tensiometers, thus it makes possible to observe the soil-plant-atmosphere system.